Measuring the impact of peacebuilding interventions on rule of law and security institutions
Since the 1990s, internationally-supported peacebuilding interventions have become increasingly prominent. Activities focusing on rule of law and security institutions are a key component of this agenda. Despite increasing calls for more rigorous analysis of the impact of peacebuilding interventions, conceptual advances have been limited. There is little clarity on what is working, what is not, and why. This SSR Paper seeks to address this gap by mapping relevant approaches and methodologies to measuring impact. It examines how international actors have approached these questions in relation to support to rule of law and security institutions in complex peacebuilding environments. Most significantly, the paper demonstrates that measuring impact is not only feasible but necessary in order to maximise the effectiveness of major international investments in this field.